1.56 µm sub-microjoule femtosecond pulse delivery through low-loss microstructured revolver hollow-core fiber. (6th February 2017) - Krylov, Alexander A; Senatorov, Andrey K; Pryamikov, Andrey D; Kosolapov, Alexey F; Kolyadin, Anton N; Alagashev, Grigory K; Gladyshev, Alexey V; Bufetov, Igor A
Abstract: We report for the first time, to the best of our knowledge, on ~1 MW peak power femtosecond pulse delivery through  ≈10 m-long air-filled microstructured revolver hollow-core fiber (RHCF) in the telecom spectral band near 1.56 µ m wavelength. We have developed a high-power all-fiber master oscillator power amplifier source based on the novel large-mode area erbium-doped double-clad fiber with 980 nm multi-mode diode pumping that emits up to 530 nJ pulses shorter than 400 fs with 1.42 W maximum average power. These pulses have been further launched into low-loss (<30 dB km −1 ) RHCF with eight non-touched cylindrical capillaries-based cladding and 61 µ m core size with more than 80% efficiency. Owing to low dispersion and nonlinearity of the RHCF developed, the output pulse characteristics (spectral and temporal) are close to the input ones for low and moderate pulse energies. However, we have observed significant nonlinear spectral filtering together with pulse shortening (down to 353 fs) at the maximum output average power of 0.94 W. We believe that the system developed may be highly promising for high-precision material processing and other high-energy and high-power laser applications.